Impact of first chemotherapy exposure on follicle activation and survival in human cryopreserved ovarian tissue. Issue 3 (1st February 2023) - Devos, Melody; Diaz Vidal, Paula; Bouziotis, Jason; Anckaert, Ellen; Dolmans, Marie-Madeleine; Demeestere, Isabelle
Abstract: STUDY QUESTION: Does chemotherapy exposure prior to ovarian tissue cryopreservation (OTC) impact the signaling pathways governing follicle activation and survival for prepubertal and postpubertal patients? SUMMARY ANSWER: Chemotherapy exposure prior OTC increases follicle apoptosis rates but not follicular activation, although the PI3K/AKT/mTOR and Hippo signaling pathways were modified in the cortex. WHAT IS KNOWN ALREADY: OTC is currently the only available fertility preservation procedure for children and for patients who have already started their treatment. While previous studies have not observed harmful impacts of first chemotherapy exposure on OTC outcomes, the consequences of treatment on follicle activation and survival need to be further investigated. To address this question, we evaluated signaling pathway modifications induced by chemotherapy exposure according to pubertal status. STUDY DESIGN, SIZE, DURATION: Cryopreserved ovarian tissues from postpubertal (12–29 years old, n = 8) and prepubertal (3–10 years old, n = 8) cancer patients donated for research were thawed and cultured for 24 h. Analyses of the survival of the follicles and stroma, and of the PI3K/AKT/mTOR and Hippo signaling pathways, were conducted at thawing and after culture. Ovarian fragments exposed to chemotherapy before collection were compared to non-exposed controls. PARTICIPANTS/MATERIALS, SETTING, METHODS: Histological investigations were performed to assess the distribution of the follicles, stroma fibrosis, vessel integrity, and apoptosis levels. It included follicular counting, collagen staining, immunostaining on CD31 and gH2AX, as well as TUNEL staining. To explore follicle activation in the different groups, the PI3K/AKT/mTOR and Hippo signaling pathways were investigated by gene expression analyses of isolated follicles and protein analyses on whole fragments through western blots and immunostaining. MAIN RESULTS AND THE ROLE OF CHANCE: We first assessed the impact of a first exposure to chemotherapy on the collagen density and vessels in ovarian tissues at thawing and after culture. While no differences in collagen density were observed according to age or previous treatment, the vascularization area (CD31+) was significantly lower in tissue from previously exposed patients compared to non-treated ones. Apoptosis analyses (TUNEL) revealed an acute deleterious impact on follicle survival after chemotherapy exposure without affecting the follicular density. Surprisingly, leukemic patients had a significantly higher percentage of gH2AX-positive follicles, indicating a DNA damage response, compared to the other patients. The proportion of activated follicles appeared to decrease following exposure to chemotherapy, suggesting that it at least did not increase activation process. Stable KIT LIGAND gene and protein expression and cKIT protein levels were observed among the groups, confirming the absence of activation. Analysis of the PI3K pathway did not reveal a difference in the AKT phosphorylation level between the groups, but pRPS6 was significantly higher in tissue from patients previously exposed to chemotherapy compared to that from non-exposed patients. Finally, protein and gene analyses on Hippo pathway signaling showed a higher LATS1 protein level in the cortex after chemotherapy exposure. LIMITATIONS, REASONS FOR CAUTION: The heterogeneity of the human fragments, and the limited number of patients included in the cohort have to be considered as important study limitations. Moreover, this study did not explore the long-term consequences of chemotherapy on follicular development. Therefore, the results should be interpreted with caution. WIDER IMPLICATIONS OF THE FINDINGS: These results underscore the deleterious effect of previous chemotherapeutic treatment on follicle survival. Although follicular density was not reduced, these data suggested that exposure to chemotherapy impacts follicular apoptosis and the DNA damage response. Chemotherapy-induced activation was not observed despite the impact on mTOR and Hippo signaling pathways in the whole cortex. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by an Excellence of Science (EOS) Grant (ID: 30443682) and was supported by Fonds Erasme. I.D. and M.-M.D. are associate researchers at Fonds National de la Recherche Scientifique de Belgique (FNRS). There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.